2009
DOI: 10.1007/s00267-008-9249-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Crowding–Satisfaction Relationship in Recreational Boating

Abstract: Along with the growing boating population and the number of boats in use on limited inland waterways, boater expectations of setting density, safety perceptions, and the associated impacts on their experience (e.g., satisfaction) are becoming increasingly important. The primary purpose of this article was to explore a recreational boating crowding-satisfaction model derived from previous work using safety and enjoyment as mediating variables. We also tested our crowding-satisfaction model among day and overnig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 47 publications
4
32
0
3
Order By: Relevance
“…Level of perceived crowding was impacted on inversely by a -0.15 significance by expectation in this study as shown by the structural model. This finding is consistent with previous research [40,41,42,43,66,67] which posit that level of crowding perception reduces from the direct impact of successfully meeting individual expectations. Past experiences of pilgrims of African origins are brought to bare in determining how they experience Hajj.…”
Section: Structural Modelsupporting
confidence: 93%
See 2 more Smart Citations
“…Level of perceived crowding was impacted on inversely by a -0.15 significance by expectation in this study as shown by the structural model. This finding is consistent with previous research [40,41,42,43,66,67] which posit that level of crowding perception reduces from the direct impact of successfully meeting individual expectations. Past experiences of pilgrims of African origins are brought to bare in determining how they experience Hajj.…”
Section: Structural Modelsupporting
confidence: 93%
“…The importance of expectation was found to decrease satisfaction in recreational boat racing participants due to the increasing crowds at the event. The participants reactions was stimulated by the close proximity to a lake and coast line with the impending disaster looming [41]. In addition, as the participants increased, there was impediments to the main events which resulted in unplanned distractions [41].…”
Section: Hajj Crowding and Personal Factors 41 Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por meio dos resultados, essa hipótese é suportada de duas formas, uma por meio da Figura 4, na qual temos um β= 0,413 (p<0,001), e outra por meio da Tabela 5, em que há uma condição isolada entre crowding e satisfação com β= 0,416 (p<0,001). Esses resultados são suportados por Tseng et al (2009) e Machleit et al (1994, pois, conforme relata em seu trabalho a existência de correlação positiva entre crowding e satisfação para os compradores do K-Mart e que um cliente pode sentir-se mais satisfeitos em uma loja de desconto quando há muitos outros compradores, porque a aglomeração humana pode indicar que há boas pechinchas a serem encontradas.…”
Section: Discussionunclassified
“…), mas encontrar uma situação de superlotação não é parte do prazer recorrente. Visto que a relação crowding-satisfação pode ser influenciada por múltiplas fontes de satisfação, outros mediadores também podem explicar porque o nível de satisfação pode permanecer alto, apesar da experiência de crowding (TSENG et al 2009). …”
Section: Conclusões Limitações E Recomendaçõesunclassified